Religious Speech Acts of Ruqyah Practitioners on YouTube and Their Educational Implications for Participants’ Religious Literacy: A Religiolinguistic Study - Slamet Kartono; Ika Septiana; Harjito Harjito (Journal of Educational Sciences, 2026)
The rapid expansion of digital media has transformed religious communication, enabling religious practices traditionally conducted offline to function as informal religious education through online platforms such as YouTube. In this context, religious language functions not only as spiritual guidance but also as an educational medium that supports the development of participants’ religious literacy. This study aims to analyze the forms of religious speech acts employed by practitioners of Jam’iyyah Ruqyah Ahlussunah Waljamaah (JRA) in digital ruqyah practices on YouTube and to examine their educational implications for participants’ religious literacy. Using a qualitative descriptive approach, data were collected from selected ruqyah videos published on the official JRA YouTube channel. The data were analyzed using pragmatic analysis based on speech act theory, focusing on illocutionary and perlocutionary dimensions. The findings show that JRA practitioners predominantly employ illocutionary speech acts, particularly directive, expressive, and representative acts. Directive acts guide ritual behavior and learning processes, expressive acts foster emotional and spiritual engagement, and representative acts reinforce religious knowledge. The perlocutionary effects include increased religious understanding, ritual awareness, self-reflection, and strengthened religious literacy among participants. This study contributes to religiolinguistics and educational studies by demonstrating the role of religious speech acts in digital media as a medium for informal religious learning.